2005
DOI: 10.1016/j.cell.2005.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Methylation by Set2 Directs Deacetylation of Coding Regions by Rpd3S to Suppress Spurious Intragenic Transcription

Abstract: Yeast Rpd3 histone deacetylase plays an important role at actively transcribed genes. We characterized two distinct Rpd3 complexes, Rpd3L and Rpd3S, by MudPIT analysis. Both complexes shared a three subunit core and Rpd3L contains unique subunits consistent with being a promoter targeted corepressor. Rco1 and Eaf3 were subunits specific to Rpd3S. Mutants of RCO1 and EAF3 exhibited increased acetylation in the FLO8 and STE11 open reading frames (ORFs) and the appearance of aberrant transcripts initiating within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

74
1,338
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,196 publications
(1,440 citation statements)
references
References 68 publications
(93 reference statements)
74
1,338
4
1
Order By: Relevance
“…3). Based on the recent evidence that Set2p-mediated methylation of H3K36 is involved in the recruitment of a repressive Rpd3 complex (35)(36)(37), the simplest explanation of these observations is that this complex negatively regulates both meiotic recombination and transcription. This negative regulation is likely to be a consequence of a closed chromatin structure caused by Rpd3p-mediated deacetylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Based on the recent evidence that Set2p-mediated methylation of H3K36 is involved in the recruitment of a repressive Rpd3 complex (35)(36)(37), the simplest explanation of these observations is that this complex negatively regulates both meiotic recombination and transcription. This negative regulation is likely to be a consequence of a closed chromatin structure caused by Rpd3p-mediated deacetylation.…”
Section: Discussionmentioning
confidence: 99%
“…HIS4 hotspot in wild-type, set2, rpd3, and set2 rpd3 strains Loss of the Rpd3p deacetylase results in increased acetylation of many sites in H3 and H4 histones (56,57), whereas loss of the Set2p methylase directly affects only methylation of H3K36 (34). The Set2p-mediated methylation, however, helps recruit a repressive Rpd3p-containing complex to chromatin, and elevated histone acetylation was observed for several loci in set2 mutant strains (35,37). Consequently, we examined the histone acetylation levels at H3K27 by chromatin immunoprecipitation (ChIP analysis) in the diploids FX1 (wild-type), JDM1093 (set2), JDM1095 (rpd3), and JDM1096 (set2 rpd3).…”
Section: Measurement Of Meiosis-specific Dsbs At Thementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in yeast have shown that methylation of H3-K36 by SET2 recruits histone deacetylase to transcribed regions and links to phosphorylation of the C-terminal domain of RNA polymerase II and the process of transcriptional elongation (Carrozza et al, 2005;Joshi and Struhl, 2005;Keogh et al, 2005). Of interest, Carrozza et al reported that the histone deacetylation occurs at coding regions and suppresses intragenic transcription.…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…(ii) The evicted histones are tethered to histone chaperones and Pol II advances along the ORF. (iii) The histones are reassembled in the wake of elongating Pol II, and the resultant nucleosomes are deacetylated [39]. The process is repeated when Pol II reaches the next nucleosome, which has been depicted to contain H3K36me (purple circle) to illustrate possible events at the 3’ ORF, where H3K36me may aid in recruitment of NuA3.…”
Section: How Could Histone Acetylation Promote Histone Eviction?mentioning
confidence: 99%